Seawater Quality Parameters in Whale Shark Tourism Area in Bontubarani Waters, Gorontalo Province - Katarina Hesty Rombe; Agus Surachmat; Melda Salsabila K (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
The appearance of whale sharks in several waters in Indonesia has now encouraged the development of tourism activities based on whale sharks. One area that has become a tourist destination for whale sharks both locally and abroad is Botubarani Waters, Gorontalo. Some experts reveal that the presence of whale sharks is influenced by environmental factors, such as salinity, temperature and pH. This study was aimed to measure the value of water quality (temperature, salinity and pH) in the Botubarani whale shark tourist area, Gorontalo so as to create a balance between whale shark tourism and the preservation of the tourist attraction itself. This research was conducted in Botubarani waters, from 8 March to 8 April 2020. The data collection of temperature, salinity and pH was carried out for 30 days. The data collection point is the area where whale sharks were found to surface. Data were collected on temperature, salinity and pH, respectively, using alcohol thermometer, seawater hydrometer and pH test paper. The results showed that the temperature values in Botubarani waters ranged from 24-30.3 ºC, salinity ranged from 33-36 ppt and pH 7. The conditions of Botubarani waters (temperature, salinity and pH) were still in the optimal category for both whale sharks and marine tourism